Effects of single- and multi-energies ion irradiations on clustering in an Fe–Mn–Ni–Si alloy - Yang Kong; Yue Sun; Shenbao Jin; Gang Sha (Journal of Materials Research and Technology)
The effects of single- and multi-energy self-ion irradiations on clustering in an Fe–Mn–Ni–Si alloy have been carefully investigated using atom probe tomography. The two irradiation approaches produce distinct clustering nanostructures, differing in cluster number density, average size and chemical composition. These variations are influenced significantly by factors such as irradiation dose, implanted ion content, reheating and subsequent low-energy irradiation. Notably, reheating during multi-energy irradiation dissolves large, high-density irradiation clusters while small, low-density clusters remain largely unaffected. Subsequent low-energy irradiation promotes the nucleation of new small clusters at sites where large clusters dissolved, with these new clusters exhibiting a similar composition to the original ones. The uniform damage region achieved through multi-energy irradiation is identified as optimal for correlating irradiation-induced clusters with material hardening, offering a reliable basis for nanoindentation testing and further microstructural characterization.